2020
DOI: 10.1155/2020/9673289
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Distribution of Atmospheric Ducts in Alaska and Its Relationship with the Arctic Vortex

Abstract: In Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Kohma et al [26] mentioned that seasonal variation in radar-based ε shows a broad maximum in August-October and low values in November-January in the lower stratosphere, which is similar to our results. The statistical characteristics of gravity waves at Gadank, which has the same latitude as Guam, are discussed in detail in [53][54][55], which have a certain reference significance for the turbulence distribution characteristics in this paper. Clear seasonal variation in the wave activity was noted in their study, and during the monsoon season, they found that the significant enhancement of gravity wave activity was related to the westward phase of the zonal wind.…”
Section: Overview and Discussionmentioning
confidence: 99%
“…Kohma et al [26] mentioned that seasonal variation in radar-based ε shows a broad maximum in August-October and low values in November-January in the lower stratosphere, which is similar to our results. The statistical characteristics of gravity waves at Gadank, which has the same latitude as Guam, are discussed in detail in [53][54][55], which have a certain reference significance for the turbulence distribution characteristics in this paper. Clear seasonal variation in the wave activity was noted in their study, and during the monsoon season, they found that the significant enhancement of gravity wave activity was related to the westward phase of the zonal wind.…”
Section: Overview and Discussionmentioning
confidence: 99%
“…Using numerical model simulations, most previous studies only found significant regional surface responses over the northern middle and high latitudes when comparing cases of extremely high and low Arctic stratospheric ozone (Cheung et al 2014;Karpechko et al 2014;Smith and Polvani 2014;Calvo et al 2015;Xie et al 2016Xie et al , 2017Harari et al 2019). One possible reason is that the dynamical variability of the Arctic stratospheric polar vortex is much larger than its Antarctic counterpart (Hu and Guan 2018;Hu et al 2019a;Mai et al 2020) and as a result Arctic stratospheric ozone depletion is less persistent than Antarctic ozone depletion (Manney et al 2011). Therefore, one would expect a weaker impact of ozone depletion on surface conditions in the Northern Hemisphere compared to the Southern Hemipshere.…”
Section: Introductionmentioning
confidence: 99%
“…An atmospheric gravity wave is a disturbance phenomenon with vertical propagation properties which plays an important role in global meteorology, climatology, chemistry, and stratosphere dynamics (Holton, 1983;Fetzer and Gille, 1994;Bai et al, 2017). With the development of observational methods (Chang et al, 2020;Mai et al, 2020;Sheng et al, 2020), gravity waves can now be extracted in different ways (He et al, 2020). The most important sources of gravity waves include topography, convection, and wind shear.…”
Section: Introductionmentioning
confidence: 99%